2020
DOI: 10.1016/j.annpal.2020.102444
|View full text |Cite
|
Sign up to set email alerts
|

Review of the paleobiogeography of Eofavartia Merle, 2002 (Gastropoda: Muricidae) with the description of a new species from the Miocene of Java (Indonesia)

Abstract: The paleobiogeographic range of Eofavartia Merle, 2002 (Gastropoda: Muricidae) was until now restricted to the Eocene (Ypresian to Priabonian) of the North Atlantic Ocean and the genus seemed to become extinct after the Priabonian. The description of E. dharmai nov. sp. from the Middle Miocene from Java (Indonesia) reveals the persistence of Eofavartia during the Neogene in the Indo-Pacific region. In addition, the revision of three South Australian species previously attributed to Murexiella and Subpterynotus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Several previous researchers who have studied the intervals of the lower Middle Miocene of Nyalindung Formation generally concluded that shallow seas dominated the depositional environment . The researchers include Aswan and Ozawa (2006), Clements and Hall (2007), Firmansyah et al (2017), Putri (2019), Merle andLandau (2020), andKesuma (2020). Based on the findings on the Nyalindung Formation in the Ciodeng River section at the beginning of the Late Miocene, it can be seen that there are indications of shallowing sea level due to environmental changes compared to the Middle Miocene interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous researchers who have studied the intervals of the lower Middle Miocene of Nyalindung Formation generally concluded that shallow seas dominated the depositional environment . The researchers include Aswan and Ozawa (2006), Clements and Hall (2007), Firmansyah et al (2017), Putri (2019), Merle andLandau (2020), andKesuma (2020). Based on the findings on the Nyalindung Formation in the Ciodeng River section at the beginning of the Late Miocene, it can be seen that there are indications of shallowing sea level due to environmental changes compared to the Middle Miocene interval.…”
Section: Discussionmentioning
confidence: 99%
“…Putri (2019) studied the paleoecology of the depositional environment of the Nyalindung Formation in the Cijarian River. Merle and Landau (2020) examined the presence of the Eofarvatia fossil in the Nyalindung Formation as evidence of the continuity of the Tethys shallow marine system during the Neogene in the Indo-Pacific region. Kesuma (2020) researched paleo-currents during the deposition of the Nyalindung Formation in the Cigalasar River section.…”
Section: Introductionmentioning
confidence: 99%